Leveraging stakeholder engagement dimensions for Solar Photovoltaic (PV) project success: A case study in Pahang, Malaysia - Zarith Sufia, Azlan; Noorzihan, Abd Karim (GBMR, 2025)
Purpose: The main aim of this study is to investigate the effect of stakeholder engagement dimensions on the success of Solar PV projects in Pahang.